Pre-transplant IE1-specific T-cell response and CD8+ T-cell count as predictive markers of treated HCMV reactivation in kidney transplant recipients - Zavaglio, Federica; Cassanti, Irene; Gregorini, Marilena; Grignano, Maria Antonietta; Rampino, Teresa; Lilleri, Daniele; Baldanti, Fausto (Frontiers in Immunology, 2025)
BackgroundHuman cytomegalovirus (HCMV) infection represents a significant complication for kidney transplant recipients (KTRs). The goal of this study was to evaluate potential immunological markers at pre-transplant in HCMV-seropositive KTRs for predicting HCMV severe reactivation (e.g treated HCMV reactivation) during the first year after transplant.MethodsBefore transplant, lymphocyte count was measured in whole blood and HCMV-specific T-cell response was determined using ELISpot assay after stimulation with pp65, IE-1 and IE-2 peptides pool. HCMV DNA was monitored during the first year after transplant. Among the 65 KTRs enrolled, 44 (68%) patients had HCMV self-resolving reactivation (Controllers) while 21 (32%) required antiviral treatment for HCMV reactivation (Non-Controllers).ResultsNo significant difference in CD4 T-cell count was observed, but Controllers had higher CD8+ T-cell counts compared to Non-Controllers. Based on ROC analysis, a CD8+ T-cell count ≥215 cells/μl was associated with a lower incidence of HCMV reactivation after transplant. Additionally, a higher IE-1-specific T-cell response was observed in Controllers and patients with IE1-specific T-cell response ≥60 spots showed a reduced incidence of HCMV reactivation and lower DNAemia peak.DiscussionLymphocyte counts and HCMV-specific T-cell response can be measured at pre-transplant in KTRs in order to efficiently predict the risk of treated HCMV reactivation during the first year after transplant. Potential cut-off and diagnostics algorithm should be better investigated in a large patients setting.